Ternary complexes of copper(II) and cobalt(II) carboxylate with pyrazole based ligand: Syntheses, characterization, structures and bioactivities. (14th December 2015) - Solanki, Ankita; Sadhu, Mehul H.; Patel, Shweta; Devkar, Ranjitsinh; Kumar, Sujit Baran
Graphical abstract: Seven ternary complexes of Cu(II) and Co(II) carboxylate with tetradentate N4 coordinate ligand have been synthesized and characterized with structures. Antimicrobial activity of all complexes were screened against Gram positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram negative ( Escherichia coli and Pseudomonas aeruginosa ) bacterial strains and cytotoxic activity of two copper complexes were studied against A549 lung carcinoma cancer cells. Abstract: A series of seven mononuclear ternary complexes of the types [Co(CH3 COO)(dbdmp)]PF6 and [M(X)(dbdmp)]ClO4 where M = Cu(II) and Co(II), dbdmp =  N, N -diethyl- N ′, N ′-bis((3, 5-dimethyl- 1H -pyrazol-1-yl)methyl)ethane-1, 2-diamine, X = Cl3 CCOO −, C6 H5 COO − and C6 H4 (OH)COO − have been synthesized and characterized by spectral data, microanalyses, EPR and electrochemical studies. Crystal structures of two copper(II) complexes [Cu(Cl3 CCOO)(dbdmp)]ClO4 and [Cu(C6 H5 COO)(dbdmp)]ClO4 and three cobalt(II) complexes [Co(X)(dbdmp)]ClO4, where X = Cl3 CCOO −, C6 H5 COO − and C6 H4 (OH)COO − have been determined by single crystal X-ray diffraction studies and showed that all the complexes have distorted trigonal bipyramidal geometry. The EPR spectra of copper(II) complexes in CH3 CN solution at 77 K exhibit spectra with characteristic d x 2 - y 2 ground state. Electrochemical studies of copper(II) complexes using glassy carbon electrode in acetonitrile solution show Cu(II)/Cu(I) couple with quasi reversible electron transfer. Antimicrobial study of all copper(II) and cobalt(II) complexes were investigated against Gram positive and Gram negative bacteria. The cytotoxic activity of copper(II) complexes [Cu(C6 H5 COO)(dbdmp)]ClO4 and [Cu(C6 H4 (OH)COO)(dbdmp)]ClO4 have been explored against A549 lung carcinoma cancer cells.